Coach autonomy support predicts autonomous motivation and daily moderate-to-vigorous physical activity and sedentary time in youth sport participants - Fenton, S.; Duda, J.; Quested, Eleanor; Barrett, T. (2014)
Objective: Guided by self-determination theory (Deci & Ryan, 1987), this study tested a trans-contextual model linking perceptions of the social environment created by the youth sport coach to levels of autonomous and controlled motivation, and objectively measured daily moderate-to-vigorous physical activity (MVPA) and sedentary time (ST) in young football players. Design: The study employed a cross-sectional design, assessing physical activity using accelerometers. Method: 105 male youth sport footballers (M age = 12.79 ± 1.85 years) wore a GT3X accelerometer for 7 days. Measures of height and weight were recorded. Participants completed a multi-section questionnaire assessing perceptions of autonomy support and controlling coaching behaviours, and motivation toward their participation in sport and physically active games. Results: Path analysis supported a model in which players' perceptions of coach-provided autonomy support positively predicted autonomous motivation for sport engagement. In turn, autonomous motivation was positively associated with MVPA, and negatively related to ST (min/day). Controlling coach behaviours were positively linked to controlled motivation. However, controlled motivation for sport and physically active games was unrelated to daily MVPA and ST. Perceptions of coach-provided autonomy support had a significant positive indirect effect on daily MVPA, and a significant negative indirect effect on daily ST. Conclusions: Results suggest that autonomy supportive coach behaviours are related to daily physical activity patterns in young male footballers. Theory-based interventions that aim to encourage autonomy supportive coaching, and subsequently foster autonomous reasons for sport engagement, may enhance the potential of youth sport for increasing daily MVPA and reducing ST among children and adolescents active in this setting. © 2014 Elsevier Ltd.